The Influence of Digital Comics in Teaching Grammar for EFL Students during the COVID-19 Pandemic : Pengaruh Komik Digital dalam Pengajaran Grammar untuk Siswa EFL selama Pandemi COVID-19 - Rifki Arya Sandika; Dian Novita (Academia Open, 2021)
This research aims to identify the influence of digital comic media on EFL students' grammatical knowledge during the COVID-19 pandemic. The approach used in this research is quantitative which data collection techniques used pre-test, treatment, and post-test. This research used 21 students of class VIII-C as research subjects at MTs Maarif NU Ngaban academic year 2021-2022. The results of this study showed mean score on student learning outcomes increased by 61,4%. Moreover, the results of hypothesis testing show the value of Sig. (2-tailed) was 0,000 < 0,005, so H0 is rejected. This means that the results of the research show that there is a significant impact on the use of digital comics as a medium for teaching grammar at MTs Maarif NU Ngaban academic year 2021-2022.